Emergency Treatment for Central Retinal Artery Occlusion (CRAO) - Nida Farida (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2020)
Central retinal artery occlusion (CRAO) is a blinding event but not considered as a common emergency problem. Since awareness of the case is low, patients usually come to the ophthalmologist later than the golden period and havingthe worst prognosis. We report the case of patient with a central retinal artery occlusion that had visual improvement after emergency treatment.A 47-year-old woman with no comorbidities presented with symptoms of a sudden blurred vision, no pain or redness in the right eye (RE). Best-corrected visual acuity in the RE was 1/60. A relative afferent pupillary defect was observed in the RE. Ocular fundus examination of RE was suggestive of CRAO. Emergency treatment were performed, including rebreathing of expired CO2, ocular massage and ocular chamber paracentesis. One week later, the visual acuity was improved.This case highlights that fast and accurate response in acute management of CRAO should be conducted, especially within the golden hours which is less than 6 hours after the accident, to prevent permanent visual loss of thepatient.